Determinants of length of stay : a parametric survival analysis - Menezes, António Gomes de (2006)
Length of stay is one of the most important decisions made by tourists as it conditions their overall expenditure and stress caused on local resources. This paper estimates survival analysis models to learn the determinants of length of stay as survival analysis naturally lends itself to study the time elapsed between arrival and departure at a destination. It is found that individual sociodemographic profiles, such as nationality and gender, and attributes of actual trip experiences, such as repeat visitor behavior and overall satisfaction, are important determinants of length of stay. Thus, this paper’s regression results can be used to estimate the probability that a given group of individuals experiences a stay longer than a given threshold. This is important to the design of marketing strategies that effectively influence length of stays.